The employment of metaphors in Najib's speeches on economy - Jasman, Nurul Hijah; Mohd Kasim, Zalina (Malaysian Association of Modern Languages, 2014)
The cognitive and affective appeal of metaphor exploits subconscious discernment that is aroused non-verbally and then developed through language. It is the subliminal potential of metaphor that reinforces the performance of leadership and this explains the frequent usage of such rhetorical tool in speeches by many politicians (Charteris-Black 2011: 2). This study examines metaphors in the speeches of the sixth Prime Minister of Malaysia on the Economic Transformation Programme (ETP). The cognitive metaphor framework by Lakoff and Johnson (1980) has been utilised in examining any emerging patterns from the PM’s speeches. The Metaphor Identification Procedure (MIP) as proposed by Pragglejazz Group (2007) has been adopted in the analysis of the data. The results from the analysis have shown several interesting conceptual metaphors underlying some of the metaphorical expressions in the speeches by the Prime Minister, including the ECONOMY IS A SPORT conceptual metaphor. Such findings have provided some insights into the way conceptual metaphors are used in political speeches as a way to evoke certain understanding of concepts related to the economy and also as a mechanism of persuasion.